Graphic Design Analysis of the Nickelodeon Animated Film Poster Plankton: The Movie (2025) - Ismoyo, Katrin Nur Nafi’ah (Green Publisher Indonesia, 2025)
Science has always evolved, ranging from technical science to creativity. One of the sciences that cultivates creativity is fine art, in this study focuses on fine art (graphic design). This study analyzed the 2025 movie poster